Three-dimensional soft tissue changes according to skeletal changes after mandibular setback surgery by using cone-beam computed tomography and a structured light scanner - Kyung-A Kim; Ye-Jin Chang; Su-Hyun Lee; Hyun-Joon An; Ki-Ho Park (SpringerOpen, 2019)
Abstract Background To evaluate the three-dimensional (3D) changes after mandibular setback surgery (MSS) in skeletal Class III malocclusion using cone-beam computed tomography (CBCT) and a structured light-based scanner. Methods Twenty-eight adult Korean patients with skeletal Class III malocclusion treated by MSS were evaluated. CBCT and facial scan images were recorded one week before and six months after surgery. To use an identical 3D coordinate system, superimposition was performed, and nine skeletal and 18 soft tissue landmarks were identified. Changes in the landmarks and correlation coefficients and ratios between hard and soft tissue changes were evaluated. Paired t test and Pearson's correlation test were performed. Results After MSS, the amount of transverse correction was 2.45 mm; mandibular setback, 5.80 mm; and vertical reduction, 1.64 mm at the menton, on average. In the transverse axis, there were significant changes and correlations in the lips and chin and an increasing gradient of ratios from the lower lip to the chin. In the anteroposterior axis, the lower lip and chin moved backward significantly and showed notable correlation with hard tissue movement. In the vertical axis, significant upward movement was observed in the landmarks related to the chin, but only lower facial height was significantly decreased. Conclusions Soft tissue changes according to hard tissue movement after MSS exhibited a distinct pattern of an increasing gradient from the lips to the chin in a transverse aspect.